The Impact of Significant Risk Factors on the Mortality Rate of Hospitalized COVID-19 Patients in the Iranian Population - Nasrin Milani; Mohammad Rouhbakhsh Zahmatkesh; Mona Kabiri (Patient Safety and Quality Improvement Journal, 2025)
Introduction:The present study aimed to assess the respiratory signs and laboratory parameters in COVID-19 patients based on recovery or mortality during hospitalization in the Iranian population. Materials and Methods: 623 patients over 16 years of age with confirmed COVID-19 infection using polymerase chain reaction test who were admitted to the COVID-19 wards of Imam Reza Hospital from 2020 to 2022 were included in this study. The vital signs and paraclinical parameters such as liver and renal function tests as well as hematological and inflammatory markers were evaluated based on recovered or non-recovered patients during admission. Results: According to our results, 135 COVID-19 patients (21.7%) expired, while 488 patients recovered through hospitalization. The frequency of acute kidney injury was significantly higher in unrecovered COVID-19 patients (71.1%) compared to the recovered group (27.3%) (p<0.001). Significant differences were found in terms of AST, direct and total bilirubin, creatinine, BUN, albumin, LDH, and CRP, as well as potassium, phosphorus, calcium, pH, HCO3, and INR serum levels between groups at both baseline and endpoint admission. The non-recovered patients demonstrated significantly higher counts of WBC, MCV, RDW, and neutrophil, as well as significantly lower amounts of RBC, hemoglobin, platelet, lymphocyte, and MXD than the recovered group during admission. Conclusion:Our findings revealed that AKI, CRP, LDH, WBC, RDW, neutrophil, and PLT were the significant risk factors in the incidence of mortality due to COVID-19 infection in the present study. These results could be helpful in screening and managing hospitalized patients during the respiratory viral pandemic.